Linguagem erótica como mediação simbólica no Cântico Espiritual de Juan de la Cruz - Helvécio, Ítalo Prado Araújo (2024)
In this research, we seek to understand how eroticism plays the role of symbolic mediation in the poetics of the Carmelite friar and Doctor of the Church Juan de la Cruz, specifically with regard to the language of the work Cántico Espiritual. We explore the symbols that make up this work, especially the relationship between the characters Husband and Wife. To this end, we use the methodology of phenomenology of religion, investigating the influences and their intertextuality with the biblical book Song of Songs, in addition to the influences coming from secular poetry. With this, we seek to conceptualize the mystical phenomenon, starting from its historical development and its meaning for Juan de la Cruz, going through the characteristics of language and, finally, analyzing the attributes with which eroticism is presented in the poem, especially in its form and the function it plays in the Juanian composition.